“Lord, teach us the sacred words!”: some reflections concerning the Lord’s Prayer in the Heliand - Concetta Sipione (Filologia Germanica)
At the beginning of fitt XIX of the Heliand one of the disciples asks Christ to teach them how to pray to the Lord in the Heavens; in the following verses the poet adds a rendering of the Pater noster according to Matthew’s Gospel. Instead of his usual flourishing and elaborate style, the poet displays here a simpler and more sober poetic diction; at the same time the text of the prayer shows some meaningful additions and original wordings, which diverge noticeably from the Latin model. The most remarkable variations can be found in the second part of the prayer, from the fourth petition onwards, in which complex religious notions occur. The aim of this paper is to investigate these aspects of the Old Saxon translation and also to question, on the basis of some established readings of the Lord’s Prayer in Old Saxon, the occasionally misused theory of the so-called ‘Germanization’ of the Gospel.